MEMBRANE SEPARATION. I ANALOGY BETWEEN DISTILLATION “FLASH” AND COMPLETE MIXING MODULE - Armijo C., J. (2012)
This paper develops the analogy between flash distillation and membrane gas separations using a complete mixing module. Methods are provided for calculating the bubble point and the permeate flux as a function of membrane area. Example calculations are presented in the case of gas mixtures: Oxygen-Nitrogen (membrane selectivity = 2.2) and Carbon Dioxide-Methane (membrane selectivity = 31.25). The results show that the selectivity of the membrane has a marked effect on the membrane area required for the separation. Likewise, the permeate flux increases with the area of membrane but the slope of the change is strongly influenced by the selectivity of the membrane. The methods developed in this work can be easily extended to separations or multistage cascade, and for any number of components in the mixture to be separated.